Influencing Driver Offending Behavior: Using an Integrated Deterrence-based Model - Hassan, Eslam H. A. (Crime & delinquency, 2024)
Deterrence theory is the framework traditionally used to underpin road policing practices. However, there have been several developments in deterrence theory. This study uses an integrated approach and tests four hypotheses derived from classical deterrence theory, Stafford and Warr’s reconceptualization and informal sanctioning. Regression analysis of self-reported data from a sample (N = 623) of Queensland’s drivers provided evidence that punishment avoidance, both direct and vicarious, significantly predicted offending driving behaviors. Moreover, while offending driving behaviors appeared unrelated to formal sanctioning, including certainty, severity, and celerity, they were inversely associated with informal sanctions involving shame, guilt, and concern over losing the respect of friends. This indicates that policing agencies may be able to reduce road offending by implementing interventions targeted at the informal sanctions associated with these behaviors.